Application of the metaheuristic tunicate swarm algorithm in solving applied mechanics problems - Krstić, Mladen; Milenković, Branislav; Jovanović, Đorđe (Journal of Production Engineering, 2023)
In this paper, the principles of a metaheuristic algorithm based on tunicate swarm behavior are shown. The Tunicate Swarm Algorithm (TSA for short) was used for solving problems in applied mechanics (speed reducer, cantilever beam and three-dimensional beam optimization). In the end, a comparison of results obtained by TSA and results obtained by other methods is given.